Electrophysical characteristics of large-size αSi-Si(Li) detector heterostructures - Muminov, R.A.; Saymbetov, A.K.; Toshmurodov, Yo.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Electrophysical properties of large-size detector heterostructures based on a
αSi-Si(Li) have been investigated in this paper. The results prove that these detector
heterostructures are more effective as compared to the structures obtained using the
conventional diffusion technique. One can certainly predict availability of highly
effective current-voltage and capacitance-voltage characteristics in these structures.